Proceedings of the 49th Annual ACM SIGACT Symposium on Theory of Computing 2017
DOI: 10.1145/3055399.3055422
|View full text |Cite
|
Sign up to set email alerts
|

Twenty (simple) questions

Abstract: A basic combinatorial interpretation of Shannon's entropy function is via the "20 questions" game. This cooperative game is played by two players, Alice and Bob: Alice picks a distribution π over the numbers {1, . . . , n}, and announces it to Bob. She then chooses a number x according to π, and Bob attempts to identify x using as few Yes/No queries as possible, on average. An optimal strategy for the "20 questions" game is given by a Huffman code for π: Bob's questions reveal the codeword for x bit by bit. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 73 publications
(28 reference statements)
0
11
0
Order By: Relevance
“…This is due to the fact that the problem for paths is the classical binary search, where most attention received noisy comparison models, see e.g. [2,14,17,18,23,27]. As for the case of trees, they generalize binary search to searching partial orders with some interesting applications e.g.…”
Section: Related Workmentioning
confidence: 99%
“…This is due to the fact that the problem for paths is the classical binary search, where most attention received noisy comparison models, see e.g. [2,14,17,18,23,27]. As for the case of trees, they generalize binary search to searching partial orders with some interesting applications e.g.…”
Section: Related Workmentioning
confidence: 99%
“…In view of the above, it is interesting to see what types of queries can be used for constructing effective strategies? In [9] is is shown that there exists a 'natural' set of O(rn 1/r ) queries allowing for construction of strategies of length H(µ) + r, and it is also shown that this bound is asymptotically tight.…”
Section: Related Workmentioning
confidence: 99%
“…Substantial amount of research has been done on searching in sorted data (i.e., paths), which included investigations for fixed number of errors [4,35], optimal strategies for arbitrary number of errors and various error models, including linearly bounded [21], prefix-bounded [11] and noisy/probabilistic [8,29]. Also, a lot of research has been done on how different types of queries influence the search process -see [16] for a recent work and references therein. The mostly studied comparison queries for paths have been extended to graphs in two ways.…”
Section: Related Workmentioning
confidence: 99%